Management Strategies for Lamb Production on Pasture-Based Systems in Subtropical Regions: A Review - Poli, Cesar Henrique Espírito Candal; Monteiro, Alda Lucia Gomes; Devincenzi, Thais; Albuquerque, Fernando Henrique Melo Andrade Rodrigues de; Motta, Juliano Henriques da; Borges, Luiza Ilha; Muir, James Pierre (Frontiers in Veterinary Science, 2020)
Sheep production on pasture plays an important role in subtropical climates around the world, with great economic and environmental relevance to those regions. However, this production is much lower than its true potential in subtropical regions, largely due to lack of knowledge of how to feed grazing lambs and mitigate gastro-intestinal parasite infections. Due to weather instability and high growth rate of tropical grasses, it is difficult to adjust the quality and quantity of feed consumed by lambs. In addition, due to warm, wet weather during spring, summer and autumn, gastro-intestinal parasite infection can be intense on subtropical pastures. Thus, the objective of this paper is to summarize 17 years of research in southern regions of Brazil testing alternative management for sheep farmers under these challenging conditions. Our review indicates that ewes play important roles raising their lambs. Besides protecting and providing milk, they leave a better pasture structure for lamb nutrition. The use of creep-feeding and creep-grazing are additional alternatives to improve lamb growth. However, feeding supplementation with concentrate can deteriorate pasture quality at the end of the summer-autumn season. Gastro-intestinal parasitic infections can be reduced with improved lamb nutrition, although L3 larvae of Haemonchus contortus can be present at various pasture heights. This indicates that it is difficult to control L3 ingestion solely by manipulating grazing heights. We summarize important technologies for raising lambs on pasture-based systems to make the best of high herbage growth and minimize intense parasitic infections common in subtropical regions. We discuss research results in light of the latest studies from other ecoregions and climates, although there is a lack of similar research in subtropical regions of the world.